A group randomised trial of two methods for disseminating a smoking cessation programme to public antenatal clinics: effects on patient outcomes. Issue 2 (24th March 2006) - Campbell, E; Walsh, R A; Sanson-Fisher, R; Burrows, S; Stojanovski, E
Abstract : Objective: To assess the differential effectiveness of two methods of disseminating a smoking cessation programme to public hospital antenatal clinics. Design: Group randomised trial. Setting: 22 antenatal clinics in New South Wales, Australia. Intervention: Clinics were allocated to a simple dissemination (SD) condition (11 clinics) which received a mail-out of programme resources or to an intensive dissemination (ID) condition (11 clinics) which included the mail-out plus feedback, training, and ongoing support with midwife facilitator. Main outcome measures: Independent cross sectional surveys of women on a second or subsequent visit undertaken pre-dissemination and 18 months after dissemination. Outcomes were: (1) levels of smoking status assessment by clinic staff; (2) proportion of women identifying as having been smokers at their first visit who reported receiving cessation advice; (3) proportion of these women who had quit (self report and expired air carbon monoxide (CO)); and (4) smoking prevalence among all women (self report and CO). Subjects: 5849 women pre-dissemination (2374 SD, 3475 ID) and weighted sample of 5145 women post-dissemination (2302 SD, 2843 ID). Results: There were no significant differences between the groups on change on any outcome. Change in either group was minimal. In the post-dissemination survey, the cessation proportions were 6.4% (SD) and 10.5% (ID). Conclusions: Relatively modest strategies for encouraging incorporation of smoking cessation activities into antenatal care were not effective in the long term. Alternative strategies should be implemented and evaluated. The findings reinforce the importance of a whole population approach to tobacco control.